2019
DOI: 10.21037/qims.2018.12.10
|View full text |Cite
|
Sign up to set email alerts
|

Association between oncogenic RAS mutation and radiologic-pathologic findings in patients with primary rectal cancer

Abstract: Background: To evaluate the association between various radiologic-pathologic findings and oncogenic Kirsten-ras (KRAS) mutation in patients with primary rectal cancer. Methods: Seventy-five patients with primary rectal cancer who had undergone rectal magnetic resonance imaging (MRI) were included. The rectal MRI consisted of T2-weighted images in three planes, pre-and postcontrast-enhanced T1-weighted images, and axial diffusion-weighted images (b factors, 0, 1,000 s/mm 2). Two radiologists reviewed the MRI s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…Shin et al found that tumors with KRAS mutations exhibited a longer axial length, as well as a larger ratio of the axial to the longitudinal dimensions on pretreatment rectal MRI [ 72 ]. With an accuracy of 0.640 (95% CI, 0.520 to 0.747, p = 0.0292), the study Jo et al confirmed these findings [ 73 ]. Xu et al reported that lower Max-ADC, Mean-ADC, pure diffusion, and higher pseudo-diffusion coefficient values were demonstrated in the KRAS mutant group [ 74 ].…”
Section: Radiogenomics In Colorectal Cancermentioning
confidence: 62%
“…Shin et al found that tumors with KRAS mutations exhibited a longer axial length, as well as a larger ratio of the axial to the longitudinal dimensions on pretreatment rectal MRI [ 72 ]. With an accuracy of 0.640 (95% CI, 0.520 to 0.747, p = 0.0292), the study Jo et al confirmed these findings [ 73 ]. Xu et al reported that lower Max-ADC, Mean-ADC, pure diffusion, and higher pseudo-diffusion coefficient values were demonstrated in the KRAS mutant group [ 74 ].…”
Section: Radiogenomics In Colorectal Cancermentioning
confidence: 62%
“…KRAS mutation is associated with morphologic tumor growth patterns. Moreover, increased cell growth activity induced by activated KRAS mutation seems to be essential for polypoid growth in CRC [ 14 ]. Then, the Diffusion-Weighted imaging (DWI) that offers functional quantitative information on the tissue’s microstructure by means of the water proton mobility differences and cellular density evaluation [ 15 , 16 ] can be used in the detection of RAS mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies (274 patients) analyzed associations between ADC values and KRAS status in RC [19,32,47]. Mutated RC (n = 124, 45.3%) had the calculated mean ADC value (×10 −3 mm 2 /s) of 1.12, 95% CI (0.93, 1.30) (Fig.…”
Section: Adc and Histopathological Markers In Rcmentioning
confidence: 99%